PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN AKUNTANSI (STUDI EMPIRIS PADA GURU SMK SE KOTA SEMARANG) - Sri Kustini; Ahmad Nurkhin (Dinamika Pendidikan)
This paperhas objectives firstly, to explore the use of information and communication technology in accounting learning by vocational high schools used by vocational high schools teachers in Semarang City. The result showed that there were three ICT which mostly used by the accounting teacher. They were spreadsheet software like MS Excel to save grad, notes, etc, etc., computer laboratory based on learning, and word software like MS Word. Meanwhile, the most rarely ICT used by them were teleconference based on learning, online discussion with colleges and data analysis software like SPSS program. The complementary result showed that there was no significant  difference of ICT used by them were teleconference based on learning, online discussion with colleges and data analysis software like SPSS program. The complementary result showed that there was no significant difference of ICT used by teachers based on gender and teacher certification. This research suggests the decision makers to improve the intensity and quality of ICT in accounting learning process. Thus; it is expected that the further research can explain the determinant use of ICT